Antibacterial Composite Materials Based on the Combination of Polyhydroxyalkanoates With Selenium and Strontium Co-substituted Hydroxyapatite for Bone Regeneration - Marcello, Elena; Maqbool, Muhammad; Nigmatullin, Rinat; Cresswell, Mark; Jackson, Philip R.; Basnett, Pooja; Knowles, Jonathan C.; Boccaccini, Aldo R.; Roy, Ipsita (Frontiers in Bioengineering and Biotechnology, 2021)
Due to the threat posed by the rapid growth in the resistance of microbial species to antibiotics, there is an urgent need to develop novel materials for biomedical applications capable of providing antibacterial properties without the use of such drugs. Bone healing represents one of the applications with the highest risk of postoperative infections, with potential serious complications in case of bacterial contaminations. Therefore, tissue engineering approaches aiming at the regeneration of bone tissue should be based on the use of materials possessing antibacterial properties alongside with biological and functional characteristics. In this study, we investigated the combination of Polyhydroxyalkanoates (PHAs) with a novel antimicrobial hydroxyapatite containing selenium and strontium. Strontium was chosen for its well-known osteoinductive properties, while selenium is an emerging element investigated for its multi-functional activity as an antimicrobial and anticancer agent. Successful incorporation of such ions in the hydroxyapatite structure was obtained. Antibacterial activity against S. aureus 6538P and E. coli 8739 was confirmed for co-substituted hydroxyapatite in the powder form. Polymer-matrix composites based on two types of PHAs, P(3HB) and P(3HO-co-3HD-co-3HDD), were prepared by incorporation of the developed antibacterial hydroxyapatite. An in-depth characterization of the composite materials was conducted to evaluate the effect of the filler on the physicochemical, thermal and mechanical properties of the films. In vitro antibacterial testing showed that the composite samples induce a high reduction of the number of S. aureus 6538P and E. coli 8739 cultured on the surface of the materials. The films are also capable of releasing active ions which inhibited the growth of both Gram positive and Gram negative bacteria.